On prognosis of variation of properties of multilayer structure by preliminary processing of the substrate - Evgeny Leonidovich Pankratov (International Journal of Advances in Applied Sciences, 2022)
In this paper, we analyze the effect of the preliminary processing of substrate on the properties of the grown heterostructure. It has been shown that the growth of an epitaxial layer on a buffer layer after preliminary (before starting of growth) annealing makes it possible to decrease the value of mismatch-induced stress. An analytical approach has been introduced for the analysis of mass and heat transfer in a multilayer structure with account mismatch-induced stress.